Parental Participation in Child-Friendly School Practices at Elementary School During the Covid-19 Pandemic - Muhaimi Mughni Prayogo; Kristi Wardani (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2022)
Educational practitioners are paying more attention to the practise of distance learning, nowadays. Furthermore, the Covid-19 pandemic prompted changes to child-friendly school policies that involved parental participation in distance learning environments. The purpose of this qualitative study was to examine, using nine sub-components, how parents at Tlacap Elementary School participated in promoting Child-Friendly School (CFS) implementation during the pandemic Covid-19 timeframe. The subjects are the headmaster, program coordinator, teacher of 3rd and 5th grade, and parents of 3rd and 5th grade. It used a google form and Focus Group Discussion by google meet in the data collecting process. Data analysis was conducted through reduction, display, and generalization and verified by Miles and Huberman. Internal validation undertakes by more careful observation, member check, and use of documentation tools. The parents' participation in supporting CFS implementation during the Covid-19 pandemic at Tlacap primary school has achieved six of the nine sub-components of participation well. School programs must consider the proper duration and frequency for all parents’ backgrounds. This research results can be a consideration in developing a school-home collaboration model in primary-level distance learning in the future. Praktik pendidikan jarak jauh dewasa ini semakin banyak dikaji oleh praktisi pendidikan. Terlebih, pada masa pandemi Covid-19 yang mendorong terjadinya penyesuaian praktik sekolah ramah anak yang melibatkan partisipasi orang tua dalam setting pendidikan jarak jauh. Penelitian kualitatif ini bertujuan menganalisis partisipasi orang tua siswa dalam mendukung penerapan Sekolah Ramah Anak (SRA) pada masa pandemi di SDN Tlacap berdasarkan sembilan sub-komponen SRA. Informan terdiri dari kepala sekolah, koordinator program SRA, guru kelas 3 dan 5, serta perwakilan orang tua siswa kelas 3 dan 5 yang dipilih dengan purposive sampling. Pengumpulan data menggunakan kuisioner google form dan FGD daring melalui google meet. Analisis data dilakukan dengan reduksi data, display data, penarikan kesimpulan dan verifikasi. Penelitian ini menggunakan validitas internal melalui pengamatan lebih cermat, member check, dan penggunaan alat bantu dokumentasi. Partisipasi orang tua dalam mendukung penerapan SRA pada masa pandemi Covid-19 di SD Negeri Tlacap telah meraih enam dari sembilan sub-komponen partisipasi dengan baik. Program sekolah harus mempertimbangkan durasi dan frekuensi program parenting yang sesuai dengan berbagai latar belakang orang tua siswa. Hasil penelitian ini dapat menjadi bahan pertimbangan dalam mengembangkan model kolaborasi sekolah-rumah pada praktik sekolah ramah anak melalui pembelajaran jarak jauh di tingkat sekolah dasar di masa mendatang.